2019
DOI: 10.1109/tste.2018.2874810
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Short-Term Operation of a Cascaded Hydro-Solar Hybrid System: A Case Study in Kenya

Abstract: In this paper we propose an optimal dispatch scheme for a cascaded hybrid hydro-solar power system, i.e., a hydroelectric system coupled with solar generation, that maximises the head levels of each dam, and minimises the spillage effects. As a result more water is stored in the dams to meet a given amount of energy providing more flexibility to the system in dry months. This dispatch scheme is based on the development of a simplified hydroelectric power system model which has low computational burden and may … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…Error rate is an important index to judge the solution accuracy, which reflects the gap to the most accurate results. The variation of error rate and computation time with the number of subintervals for (12) are shown in FIGURE 12 and FIGURE 13. For the sake of analysis, we assume that qH and v are equally divided, i.e., m=n.…”
Section: A Case Amentioning
confidence: 99%
See 1 more Smart Citation
“…Error rate is an important index to judge the solution accuracy, which reflects the gap to the most accurate results. The variation of error rate and computation time with the number of subintervals for (12) are shown in FIGURE 12 and FIGURE 13. For the sake of analysis, we assume that qH and v are equally divided, i.e., m=n.…”
Section: A Case Amentioning
confidence: 99%
“…Results indicate that their coordinated operation is conducive to the minimization of wind power curtailment. Dimitra et al [12] propose an optimal dispatch scheme for a hydroelectric system coupled with solar generation, and the simulation results verify the coupling of hydropower and solar power is beneficial due to the negative correlation of rain and sunshine. Shen et al [13] presents a methodology for hydrothermal system generation scheduling considering multiple provincial peak-shaving demands.…”
Section: Introductionmentioning
confidence: 99%
“…is a good approximation of (1) as shown in [8]. The power output of each hydroelectric power plant i ∈Ñ is constrained by a minimum and a maximum output, i.e., P m i ≤P i (t) ≤ P M i , for all t ∈ T .…”
Section: A Hydroelectric Power Outputmentioning
confidence: 99%
“…We represent the cascading constraints by (6)- (8) and (14) for the hydroelectric plants and the pumped storage hydro plants, respectively; the relationship between the head level and live volume by (21); the power balance by (25). The lower and upper bounds of decision variables are included through (4)- (5), and (9).…”
Section: Optimal Dispatch Formulationmentioning
confidence: 99%
“…Recent studies and practices have shown that complementary energies, such as energy storage and hydropower, are effective measures to reduce the output fluctuation of a PV power plant and achieve complementary output to meet the grid connection requirements. Hydropower is the most reliable complementary energy because of its low cost, high installed capacity, good regulation performance, and high reservoir storage capacity [17][18][19][20][21]. However, hydropower stations have higher requirements on the construction sites and environmental factors, such as abundant water sources, rich precipitation, good geological foundation, and large difference in elevation.…”
Section: Introductionmentioning
confidence: 99%